2000
DOI: 10.1038/labinvest.3780064
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Overexpression Is Present in Pyoderma Gangrenosum Ulcers and Leads to Ulcer Formation in Human Skin Xenografts

Abstract: SUMMARY: ) is a potent chemotactic polypeptide for neutrophils. However, the role of this cytokine during inflammation remains unclear. Skin specimens from patients with pyoderma gangrenosum demonstrated IL-8 overexpression in skin ulcers, which suggests a role for IL-8 in the development of the disease. We therefore constructed a recombinant adenovirus expressing the complementary deoxyribonucleic acid encoding human IL-8 (IL-8/Ad5) that induces a 2000-fold increase in IL-8 expression of infected human fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 47 publications
2
80
1
2
Order By: Relevance
“…We also observed overexpression of IL-8 in the cytoplasm of macrophages scattered among the inflammatory infiltrate; it is well known that this cytokine is a potent chemotactic polypeptide for neutrophils and may also be involved in angiogenesis [14,17]. In the literature, there is evidence for a role of IL-8 in the pathogenesis of pyoderma gangrenosum, since overexpression of this chemotactic cytokine has been found immunohistochemically in dermal fibroblast from ulcers of patients affected by this disease [18,19]. We provide evidence for abundant expression of TNF-a in both epithelial cells and the inflammatory infiltrate suggesting that this potent pro-inflammatory cytokine, which leads to recruitment of inflammatory cells to areas of inflammation, could synergistically contribute to the proinflammatory pathogenetic mechanism of PV.…”
Section: Discussionsupporting
confidence: 67%
“…We also observed overexpression of IL-8 in the cytoplasm of macrophages scattered among the inflammatory infiltrate; it is well known that this cytokine is a potent chemotactic polypeptide for neutrophils and may also be involved in angiogenesis [14,17]. In the literature, there is evidence for a role of IL-8 in the pathogenesis of pyoderma gangrenosum, since overexpression of this chemotactic cytokine has been found immunohistochemically in dermal fibroblast from ulcers of patients affected by this disease [18,19]. We provide evidence for abundant expression of TNF-a in both epithelial cells and the inflammatory infiltrate suggesting that this potent pro-inflammatory cytokine, which leads to recruitment of inflammatory cells to areas of inflammation, could synergistically contribute to the proinflammatory pathogenetic mechanism of PV.…”
Section: Discussionsupporting
confidence: 67%
“…45 We previously showed that IL-8 is overexpressed in the skin of patients with pyoderma gangrenosum, a representative of neutrophilc dermatoses. 46 We also showed that overexpression of IL-8 using adenovirus vector in human skin grafted on severe combined immunodeficiency mice resulted in neutrophil-associated skin ulcer resembling pyoderma gangrenosum. 46 These findings indicate that IL-8-induced neutrophil infiltration has a role either directly or indirectly in the pathogenesis of several inflammatory skin diseases.…”
Section: Discussionmentioning
confidence: 95%
“…46 We also showed that overexpression of IL-8 using adenovirus vector in human skin grafted on severe combined immunodeficiency mice resulted in neutrophil-associated skin ulcer resembling pyoderma gangrenosum. 46 These findings indicate that IL-8-induced neutrophil infiltration has a role either directly or indirectly in the pathogenesis of several inflammatory skin diseases. As IL-8 is not produced in normal conditions, an increased amount of IL-8 in these diseases must result from dysregulation of IL-8 production.…”
Section: Discussionmentioning
confidence: 95%
“…In human skin xenografts, IL-8 overexpression induced subepidermal neutrophil accumulation and formation of ulcers resembling PG clinically and histologically. 11 Furthermore, cultured fibroblasts isolated from a PG ulcer produced high levels of IL-8, while fibroblasts from surrounding unaffected skin produced no detectable IL-8, 12 indicating local production from cells within the lesion. Raised serum concentrations of IL-8 have been reported in patients with active PG, 12 as have raised serum concentrations of cytokines IL-6, 13 and granulocyte colony-stimulating factor (G-CSF), which stimulates proliferation, differentiation and survival of neutrophils.…”
Section: Aetiopathogenesismentioning
confidence: 99%